Reductions in all‐cause and cause‐specific mortality among HIV‐infected individuals receiving antiretroviral therapy in British Columbia, Canada: 2001–20121. Issue 9 (9th June 2016) - Cheung, CC; Ding, E; Sereda, P; Yip, B; Lourenco, L; Barrios, R; Montaner, JSG; Hogg, RS; Lima, V; Moore, DM
Abstract : Objectives: Since 2006, the British Columbia HIV/AIDS Drug Treatment Program (DTP) has expanded enrolment and dramatically increased its number of participants. We examined the effect this expansion has had on the underlying cause of death in HIV‐infected individuals. Methods: We analysed data from participants aged 18 years and older in the DTP to measure 2‐year mortality rates and causes of death from 2001 to 2012. We conducted tests of trend for all‐cause and cause‐specific mortality, and compared demographics and characteristics of individuals. Cox proportional hazard models were used to determine the risk of death. Results: A total of 8185 participants received antiretroviral therapy (ART) during the study period. Mortality declined from 3.88 per 100 person‐years (PY) in 2001‐2002 to 2.15 per 100 PY in 2011‐2012 ( P  =   0.02). There were significant decreases in HIV‐related deaths (2.34 to 0.56 per 100 PY; P  =   0.02) and deaths attributable to chronic liver disease (0.20 to 0.09 per 100 PY; P  =   0.01), cardiovascular disease (0.24 to 0.05 per 100 PY; P  =   0.03) and suicides (0.47 to 0 per 100 PY; P  =   0.003). Multivariate models, adjusted for age, gender, history of injecting drug use, AIDS diagnoses and baseline CD4 cell counts, demonstrated that initiation of ART in all time periods after 2001‐2002 was independently associated with reduced mortality ( P  <   0.001). Conclusions: We observed declines in HIV‐related mortality and certain non‐HIV‐related causes of death among participants in the BC DTP from 2001 to 2012. These findings suggest that there may be broader benefits to the increasingly liberal HIV treatment guidelines, including reductions in death caused by cardiovascular disease and chronic liver disease.